An uncommon cause of laser burns: The problem may be the use of gel. (April 2014) - Kacar, Seval Dogruk; Ozuguz, Pinar; Demir, Merve; Karaca, Semsettin
Abstract Laser hair removal is the most common procedure which is usually performed on patient's demands. Even though they are usually safe and well tolerated, with the widespread use both expected and unexpected side effects can be seen. Recognizing the source of side effects is an important issue for the laser operator. In recent years, a new laser technology has been introduced to aid in pain and other side effects in laser applications. Diode laser systems are produced for this technology. The major disadvantage with this laser is the gel application during procedure. We herein report a women while on her second session for laser hair-removal procedure with a 808-nm diode laser, complicated with an epidermal burn reaction due to accumulated debris on the guide.